Pulmonary Drug Delivery: Formulations, Devices, Targeting Strategies, and Patient Compliance - Shubham Kamble; Archi Chaudhari; Diksha Mankar; Khushi Bagde (Asian Journal of Pharmaceutical Research and Development, 2025)
Pulmonary drug delivery systems (PDDS) leverage the lungs’ large surface area and rich vascularity for treating respiratory illnesses and systemic conditions. Benefits include rapid action, avoidance of first-pass metabolism, and fewer systemic side effects. PDDS are used for acute and chronic care, with new multi-drug devices improving adherence. Targeted delivery for macromolecules is evolving to boost local retention and reduce systemic exposure. Bypassing first-pass metabolism via the lungs significantly increases bioavailability, especially for vulnerable drugs like peptides. Sustained-release formulations are being developed to extend effects and improve adherence. Smart inhalers enhance monitoring and compliance. PDDS are also being explored for non-pulmonary systemic diseases, gene and RNA therapies for lung conditions, and aerosolized vaccines. Non-invasive inhalers improve patient compliance.Challenges in PDDS include airway structure affecting particle deposition, formulation issues with particle size and stability, patient technique and compliance, and drug properties impacting solubility and retention.New strategies like nanoparticles, liposomes, and other formulations enhance drug delivery. Device advancements (pMDIs, DPIs, nebulizers, smart inhalers) improve deposition and ease of use. Emerging methods like gene therapy and magnetic targeting offer precise delivery.